2015
DOI: 10.2135/cropsci2014.01.0077
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Intraplant Cotton Fiber Variability

Abstract: It is well documented that cotton fiber variability exists across and within cultivars, across environments, soil quality, biotic and abiotic stresses. Having uniform fiber quality is a primary goal for cotton breeders to enhance profitability and sustainability. The objective of this research was to identify the within‐plant variability in fiber quality of six diverse genotypes of Gossypium hirsutum and Gossypium barbasense. This research was conducted in College Station, TX, for 3 yr in 2009, 2010, and 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Several studies have reported that lint produced at a distal position relative to the main apical node tends to have lower fiber quality (Bernhardt et al, 1986;Davidonis et al, 2004;Kothari et al, 2015). It could have an impact on the fiber-to-fiber variability of fiber quality within a bale (May and Jividen, 1999;Bauer et al, 2009), and ultimately on yarn quality.…”
Section: Evaluating Within-plant Variability Of Cottonmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that lint produced at a distal position relative to the main apical node tends to have lower fiber quality (Bernhardt et al, 1986;Davidonis et al, 2004;Kothari et al, 2015). It could have an impact on the fiber-to-fiber variability of fiber quality within a bale (May and Jividen, 1999;Bauer et al, 2009), and ultimately on yarn quality.…”
Section: Evaluating Within-plant Variability Of Cottonmentioning
confidence: 99%
“…Th ese sources of variability in fi ber quality contribute to within-bale fi ber-to-fi ber variability. One of the potential strategies to minimize the variability of fi ber quality among fi bers within a bale of cotton is to optimize the within-plant variability of cotton fi ber quality.Within-plant variability of cotton fi ber quality is determined by many factors, including the growth habit of the cotton plant, genetics, and environmental conditions during cotton fi ber development (Stewart, 1975;Faulkner et al, 2011;Kothari et al, 2015). Th e indeterminate fruiting habit of the cotton plant provides a signifi cant source of within-plant variation in cotton fi ber quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macedonia and Thrace may be the best environments for cotton cultivation, due to favorable and stable performance of cultivars used in these areas. Always the growing environment affects cotton fiber quality, but main fiber traits such as length, strength and elongation are high heritable and depend on the proper genotype cultivation (Smith et al, 2010;Campbell et al, 2012;Long et al, 2013;Kothari et al, 2015).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Fiber quality is a complex of various traits, such as fiber length, strength, uniformity etc. (Poehlman and Sleper, 1995) and thus it depends on both genetic and environmental factors that influence the plant's development (Bradow and Davidonis, 2000;Campbell and Jones, 2005;Basal et al, 2009a;Kothari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%